Global, regional, and national burden of near vision loss in children and adolescents under 20 years from 1990-2021 and prediction to 2060: A cross-sectional study based on the global burden of disease study 2021. - Jing Peng; Cong Zhang; Xingying Li; Jin Tang; Xi-Yuan Zhou (PLoS ONE)
Near vision loss (NVL) has become a significant global public health concern, particularly among children and adolescents under 20 years, who face increasing academic demands and prolonged screen exposure. The COVID-19 pandemic, characterized by excessive screen time and reduced outdoor activities, has likely exacerbated this trend. This study analyzes the global, regional, and national burden of NVL from 1990 to 2021 and projects future trends up to 2060 using data from the Global Burden of Disease (GBD) Study 2021. Prevalence and Disability-Adjusted Life Years (DALYs) associated with NVL were assessed across different socioeconomic levels, and future trends were forecasted using the Bayesian Age-Period-Cohort (BAPC) model. Results indicate a significant increase in NVL cases, rising to 31.7 million in 2021, with projections reaching 33 million by 2060. A strong negative correlation was observed between the Social Development Index (SDI) and NVL burden, with Africa exhibiting the highest prevalence and Australasia the lowest. Notably, NVL burden in higher SDI regions rebounded post-COVID-19, reversing previous declining trends. Across all age groups, NVL prevalence continues to rise, with females consistently exhibiting higher rates than males. These findings underscore the urgent need for targeted public health policies and resource allocation strategies to mitigate the rising burden of NVL among children and adolescents, particularly in lower SDI regions. Addressing modifiable risk factors, promoting early interventions, and integrating vision care into public health frameworks will be crucial in managing this growing health crisis.